Peripheral T-cell lymphoma, unspecified--the analysis of the data from the Czech Lymphoma Study Group (CLSG) registry - Procházka, Vít; Trněný, Marek; Pytlík, Robert; Vášová, Ingrid; Král, Zdeněk; Belada, David; Kozák, Tomáš; Kubáčková, Kateřina; Šiffnerová, Hana; Matuška, Milan; Lysý, Milan; Bolomská, Inge; et al. (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2007)
BACKGROUND: Peripheral T-cell lymphoma, unspecified (PTCL-US) is one of the entities from the infrequent family of nodal mature T-cell lymphomas. The clinical course is aggressive, and despite multiagent chemotherapy, the median survival is about 2 years. Published data are limited to retrospective, mostly single-center studies or reviews and usually include more lymphoma subtypes. AIM: To evaluate the current treatment modalities, clinical outcome and prognostic factors in unselected, new diagnosed patients with PTCL-US in the population of the central european region (Czech Republic). METHOD: Czech Lymphoma Study Group is a national scientific organization which provides an on-line database registry which collects a data about almost all new diagnosed lymphoma patients since year 2000. All diagnostic biopsies were reviewed by a reference pathologist. RESULTS: We analyzed 63 patients with new diagnosis of PTCL-US. The median age was 59 years (25-81), chemotherapy (CHT) was administered in 56 of the 63 patients: anthracyclin-based CHT in 51%, intensive CHT in 21% and non-anthracyclin regimen was applied in 13% of the patients. The overall response rate was 74.4%, (CR in 57.4%). After a median follow-up of 19.6 months, 41% of the patients were in CR, 3.4% in PR or stable disease and 55% of the patients died. The estimated survival probability in 3 years was 36%. Clinical stage (IV) and CR achievement were found to be independent survival predictors in a multivariate analysis. CONCLUSIONS: Although the current treatment modalities are mostly ineffective in PTCL-US, appropriate intensive treatment may lead to prolonged remission but not survival.
Keywords: dospělí; Aged, 80 and over; Survival Rate; lidé středního věku; míra přežití; lidé; senioři nad 80 let; senioři; mužské pohlaví; Female; Male; Aged; Middle Aged; Adult; periferní T-buněčný lymfom; ženské pohlaví; Lymphoma, T-Cell, Peripheral; Humans